Correlation between Radiological Parameters and Functional Outcome of Healed Unstable Fracture Distal Radius after External Fixation - Shrestha, Robin; Gupta, Hemant; Kandel, Manoj (Journal of College of Medical Sciences-Nepal, 2019)
Background: Wrist fractures represent about one-sixth of all fractures seen in emergency department. The goal of treating such fractures is no longer only fracture union, but also the restoration of normal anatomy with early functional recovery, as well as full and painless motion of the wrist. In this prospective study we intend to evaluate the correlation between functional outcome and radiological parameters of the unstable fracture of the distal radius when treated with external fixator. Methods: A hospital based, observational study was conducted at department of Orthopedics, College of Medical Sciences Teaching Hospital, Bharat-pur, Chitwan, during the period of January 2011 to November 2013, 54 patients, 33 male and 21 female, with unstable fracture of the distal end of radius were treated with external fixator and followed for a period of 18 weeks. Results: The clinical and radiological outcome were evaluated on the basis of Modification, by Sar-miento et al., of the Demerit Point system of Gartland and Werley and Sarmiento et al’s modification of Lid-strom’s scoring system respectively at the end of 18 weeks. The clinical result was excellent in 25 cases, good in 19 cases and fair in eight cases. There were 8 (15.4%) excellent, 25 (48.1%) good, 15 (28.8%) fair and 4 (7.7%) poor cases according to radiological scoring. Conclusions: In this study we found no correla-tion between clinical outcome and radiological parameters following external fixation in distal radius fractures.